Simplified Audits Support Micro Small And Medium Enterprise Financial Governance: Audit Sederhana Mendukung Tata Kelola Keuangan Usaha Mikro Kecil Dan Menengah - Naning Rahmawati (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Micro, Small, and Medium Enterprises contribute 61.07% to Indonesia’s GDP and absorb 97% of the national workforce, yet 77.5% still lack adequate financial reporting. Specific Background: Most micro, small, and medium enterprises rely on manual or inconsistent bookkeeping, have limited understanding of financial standards, and experience obstacles in accessing financing due to unreliable financial statements. Knowledge Gap: Previous studies highlight financial literacy and reporting issues, but limited research explains how simplified audits aligned with national financial standards function as a practical mechanism for supporting financial governance. Aims: This literature review from 2022–2024 analyzes the urgency, mechanisms, and outcomes of simplified audits in strengthening financial management for micro, small, and medium enterprises in Indonesia. Results: Findings show simplified audits detect accounting errors, increase transparency, strengthen tax compliance, expand financing opportunities, reduce operational inefficiencies, and clarify real business conditions through digital tools that support audit trails and systematic documentation. Novelty: This study positions simplified audits as a transitional governance instrument that bridges financial illiteracy, the application of national financial standards, and the digitalization of enterprise administration, with processes adapted to the scale and constraints of small business operations. Implications: The study indicates that policy support, digital adoption, capacity building, and affordable audit services can enable long-term financial resilience, transparency, and competitiveness for micro, small, and medium enterprises in Indonesia’s economic landscape. Highlights• Routine verification identifies misstatements, tax exposure, and hidden cash flow discrepancies.• Digital accounting tools streamline documentation and strengthen audit traceability.• Audit stages offer a practical pathway for applying national financial reporting standards. KeywordsSimple Audit; Micro Small And Medium Enterprise; SAK EMKM; Financial Health; Digital Accounting